Effect of different non-genetic factors on replacement rate and its components in Sahiwal cattle - Banik, S; Naskar, S (The Indian Journal of Animal Sciences, 2011)
The effects of different non-genetic factors affecting replacing rate and its components were studied in Sahiwal cattle. Season, periods and parity were considered nongenetic factors. The period affected the replacement rate and its components significantly. Beyond fifth lactation the efficacy of cows to replace a heifer decreased gradually.